Ionization in direct frequency comb spectroscopy - Lomsadze, Bachana (Kansas State University, 2012)
Direct frequency comb spectroscopy (DFCS) is currently the highest resolution, absolute frequency spectroscopic technique known. In general, one does DFCS by scanning the repetition rate, f[subscript]r[subscript]e[subscript]p, of a comb laser and measuring fluorescence from the excited states of the specie under study. The technique has already been successfully characterized by a theoretical model that starts with the optical Bloch equations and, with a few simplifying assumptions converts them into linear coupled iterative equations. In the present work we build on that successful model to predict the characteristics of the ion yield from photoionization by the comb laser, as a function of f[subscript]r[subscript]e[subscript]p. We show that the ion spectrum yields the same atomic structure as the fluorescence spectra, but with greater efficiency. Here, we also set up an experiment and test this theory by measuring the ion signal from direct frequency comb spectroscopy. Furthermore, instead of actively controlling the frequency comb parameters, we allow them to drift, passively measuring them and the ion signal simultaneously. The experiments were found to be in agreement with theory, and the passive comb approach was found to be functional, though not as convenient as the conventional active comb.
Keywords: Frequency comb; Atomic structure; Ionization; Physics (0605)